THE MEDIATING ROLE FROM WORK MOTIVATION TOWARDS THE IMPLEMENTATION OF CORPORATE GOVERNANCE AND RSUD X'S PERFORMANCE - Riastuti Dyah Ayu Damayanti; Ratna Indrawati; Mus Aida (Dinasti Publisher, 2021)
RSUD X is a public organization which provides health services for patients and it is required to provide those services in accordance with the standards set by the Ministry of Health of the Republic of Indonesia and the Hospital Accreditation Commission and strive to implement corporate governance to optimize its performance. This research aims to analyze the affect from the implementing corporate governance and transformational leadership style to the performance of RSUD X through work motivation as an mediating variable. This research with a quantitative and survey method used the questionnaires and audit data. The population is all employees of the State Civil Apparatus at RSUD X, which are service personnel and management/administration staff. The sampling technique that used in this research was disproportionate stratified random sampling with a sample size of 200 respondents. The data analysis method through SEM-AMOS. And the research results found: There is a simultaneous and partial affect which caused by the implementation of corporate governance, transformational leadership style and work motivation to the RSUD X performance; There is a partial positive significant affect between the implementation of corporate governance and transformational leadership style on work motivation at RSUD X. Managerial implications: By improving SIMRS, communication systems and remuneration systems.